Nurturing Academic Excellence, Language Literacy, and Student Services: Cross-Case Insights from Islamic Boarding Junior High Schools - Ridwan Ali; Imron Arifin; Ali Imron; Mustingsih Mustingsih (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
In the 21st century, educational institutions face the challenge of aligning global academic standards with character integrity and institutional sustainability. To address the empirical gap in single-site studies, this multi-site research explores the implementation of Integrative Islamic Education Management across three distinct Islamic Boarding School (IBS) junior high schools in East Java. The study aims to compare how these schools simultaneously synchronize academic excellence, bilingual ecosystems, and holistic student welfare. Using a qualitative cross-case study design, the study collected data from 24 strategically selected informants through semi-structured interviews, moderate participant observation, and rigorous document analysis, followed by within-case and cross-case thematic synthesis. The findings reveal that while execution strategies vary, ranging from international curriculum adoption and data-driven acceleration programs to progressive instructional adaptation, all three schools effectively harmonize rigorous cognitive development with daily spiritual practices. Furthermore, functional language literacy is achieved through continuous residential habituation, while proactive counseling and responsive administrative governance foster psychological well-being. The study concludes that sustainable institutional quality in modern boarding schools relies on a Tawhidic Total Quality Management paradigm. By synergizing academic rigor, immersive linguistic environments, and holistic student services, faith-based schools can successfully bridge international academic competitiveness with deep-rooted Islamic character formation.